(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The complications associated with adult obesity are overwhelming nationalhealthcare systems. No country has yet implemented a successful population-level strategyto reverse the rising trends of obesity. This article presents epidemiological data on thecomplications of adult obesity and discusses some of the challenges associated withmanaging this disease at a population and individual level.